Initiation of adjuvant chemotherapy and trastuzumab for human epidermal growth receptor 2-positive early invasive breast cancer in a population-based cohort study of older women in England. Issue 5 (June 2020) - Gannon, Melissa Ruth; Dodwell, David; Jauhari, Yasmin; Horgan, Kieran; Clements, Karen; Medina, Jibby; Cromwell, David Alan
Abstract: Background: Clinical guidance on recommended treatment for older patients with breast cancer is often ambiguous, particularly in the context of comorbidities and poor functional status. Older patients, aged 70 years and over, account for a substantial proportion of women with breast cancer yet are underrepresented in randomized controlled trials. This paper investigates the initiation of adjuvant chemotherapy and trastuzumab in older patients in routine care. Materials and methods: Women, aged 50 years and over, newly diagnosed with human epidermal growth receptor 2 (HER2)-positive early invasive breast cancer from January 2014 to December 2017 were identified from the England Cancer Registry. Chemotherapy and trastuzumab use was obtained from the Systemic Anti-Cancer Therapy (SACT) dataset. Patient and tumor characteristics influential in treatment decision-making were included in multilevel mixed-effects logistic regression models. Results: 10% of women had HER2-positive tumors. Initiation of adjuvant chemotherapy and trastuzumab decreased with age from ≥70% among women aged 50–64 years to <15% among women aged 80+ years. Initiation varied additionally by tumor characteristics and number of comorbidities. Age remained a factor in treatment decisions despite favorable other factors, with lower use among women aged 70+ years. There was also marked variation across geographical regions. Conclusions: In women with operable HER2-positive early invasive breast cancer, adjuvant chemotherapy plus trastuzumab was started less frequently as age increased, regardless of tumor characteristics or comorbidity burden. There was substantial variation in the proportion of women who started these treatments across the country. Highlights: Fewer older women with operable HER2-positive early breast cancer start the most targeted oncological systemic treatment. Initiation of adjuvant chemotherapy and trastuzumab varies by clinical factors and comorbidity. Initiation also varies by age, independently of clinical factors and comorbidity. There is variation in the initiation of adjuvant chemotherapy and trastuzumab across regions. There is a need for breast cancer teams to review chemotherapy provision and the criteria for selecting patients.